A review of dynamic models and measurements in golf - McPhee, J. (Sports Engineering, 2022)
A narrative review of dynamic models of golf phenomena is presented, as well as current technologies for measuring the motions of a golfer, club, and ball. Kinematic and dynamic models of the golf swing are reviewed, including models with prescribed motions or torques as inputs, and predictive dynamic models that maximize an objective (e.g., driving distance) to determine optimal inputs or equipment designs. Impulse-momentum and continuous contact dynamic models for clubhead-ball and ball-ground impacts are described. The key observations from 172 cited references are extracted and presented, along with suggestions for future research.